1997
DOI: 10.1017/s0022215100137569
|View full text |Cite
|
Sign up to set email alerts
|

Modified tragal cartilage – temporoparietal and deep temporal fascia sandwich graft technique for repair of nasal septal perforations

Abstract: Fifteen cases of nasal septal perforation were repaired with a tragal cartilage–temporoparietal and deep temporal fascia sandwich technique using a modification of the approach previously described (Hussain and Kay, 1992). Successful closure was achieved in 14 patients (100 per cent) after an observation time of up to two years. The operative technique and advantages of the modified approach are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 6 publications
0
30
1
1
Order By: Relevance
“…The aim is to restore normal nasal physiology and function. Various methods have been developed through the years aiming to achieve this goal: the advancement and suture of the perforation border, 2 the use of an oral mucosal ap, 3 temporalis fascia graft, 4,5 conchal cartilage with perichondrium and mastoid periosteum, 6 inferior turbinate ap, 7 tragal cartilage with perichondrium and temporalis fascia, 8 bone and temporalis fascia graft, 9 acellular human dermal allograft 10 and two-stage expanded mucosal aps 11 have been described. Despite the myriad of techniques, the results of surgical closure remain less than satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to restore normal nasal physiology and function. Various methods have been developed through the years aiming to achieve this goal: the advancement and suture of the perforation border, 2 the use of an oral mucosal ap, 3 temporalis fascia graft, 4,5 conchal cartilage with perichondrium and mastoid periosteum, 6 inferior turbinate ap, 7 tragal cartilage with perichondrium and temporalis fascia, 8 bone and temporalis fascia graft, 9 acellular human dermal allograft 10 and two-stage expanded mucosal aps 11 have been described. Despite the myriad of techniques, the results of surgical closure remain less than satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors advocate using a unilateral flap 5-7 to preserve more respiratory mucosa. [17][18][19][20][21] Conchal cartilage is a good option if septal cartilage is not available. 8,9 Friedman et al 10 used inferior turbinate flaps to repair septal perforations and reported a success rate of 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions: Repair of nasal septal perforations is a challenging procedure especially in children. Good Various methods of surgical closure of the perforation have been described: advancement and suture of the perforation border [2], the use of an oral mucosal flap [3], temporalis fascia graft [4], conchal cartilage with perichondrium and mastoid periosteum [5], inferior turbinate flap [6], tragal cartilage with perichondrium and temporalis fascia [7], bone and temporalis fascia graft [8], acellular human dermal allograft [9] and two-stage expanded mucosal flaps [10] have been described. Despite the numerous techniques, there is no ideal surgery especially for larger perforations.…”
Section: Discussionmentioning
confidence: 99%
“…Meyer [22] described a 3-step procedure that achieved closure in septal perforation larger than 4.5 cm in size. Hussain and Murphy [7] described a sandwich graft technique where the tragal cartilage is placed between the temporoparietal fascia and deep temporal fascia. This autograft has a low vascular requirement and he achieved closure in all 14 patients whose perforation was less than 4 cm.…”
Section: Discussionmentioning
confidence: 99%